PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE PADA PEMBELAJARAN IPAS DI KELAS V SD NEGERI 2 KUNINGAN - Susanti, Susi; Sutisna, Atang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The current development of education has entered the media era, where the lecture method in learning should decline and be replaced by the use of various media. Therefore, researchers are interested in conducting research and development of Articulate Storyline-based learning media with the aim of finding out the development procedures and effectiveness of Articulate Storyline-based learning media in science and science learning in class V of SD Negeri 2 Kuningan. The research method used is R&D with the ADDIE model. The results of this research show that the material aspect received a very valid assessment of 92%, and the media aspect received a very valid assessment of 95%. Apart from that, the Articulate Storyline learning media has also been proven to be effective as shown by the difference in the average pretest and posttest scores of (10.26) ≥ t-table, then seen from the teacher's response, it obtained a very valid assessment of 90%, and the student response was 87% which also stated that it is very valid. Thus, the Articulate Storyline media is effective and very suitable for use in science and science learning in class V of SD Negeri 2 Kuningan.